2006
DOI: 10.1021/jm051237e
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine/Serotonin Receptor Ligands. 12:  SAR Studies on Hexahydro-dibenz[d,g]azecines Lead to 4-Chloro-7-methyl-5,6,7,8,9,14-hexahydrodibenz[d,g]azecin-3-ol, the First Picomolar D5-Selective Dopamine-Receptor Antagonist

Abstract: Hydroxylated, methoxylated, and/or chlorinated 7-methyl-5,6,7,8,9,14-hexahydrodibenz[d,g]azecines were generally synthesized out of substituted 2-phenylethylamines and isochromanones by Bischler-Napieralski cyclization of the resulting benzamides to dibenzoquinolizines and the quaternization and cleavage of the central C-N bond under Birch conditions. Chlorination of 2-phenylethylamines was useful for the site direction of cyclization, but chlorine atoms were removed under Birch conditions so that chlorination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 15 publications
2
15
0
Order By: Relevance
“…1‐Isochromanone ( 4c ) was prepared according to the literature,14 by oxidizing isochromane with NaClO 2 and N ‐hydroxyphthalimide in CH 3 CN/H 2 O (66 % yield). Compounds 1b ,15a 2b ,15b 3b ,15c 4b ,15d 5b ,8 7b ,15e 9b ,15f 10b ,15g 4c ,14 6c 15h and 9c 15i exhibit physical and spectral properties in accord with those reported previously.…”
Section: Methodssupporting
confidence: 87%
“…1‐Isochromanone ( 4c ) was prepared according to the literature,14 by oxidizing isochromane with NaClO 2 and N ‐hydroxyphthalimide in CH 3 CN/H 2 O (66 % yield). Compounds 1b ,15a 2b ,15b 3b ,15c 4b ,15d 5b ,8 7b ,15e 9b ,15f 10b ,15g 4c ,14 6c 15h and 9c 15i exhibit physical and spectral properties in accord with those reported previously.…”
Section: Methodssupporting
confidence: 87%
“…A new D 5 R antagonist (LE-PM436) 28 was utilized to distinguish signaling of D 5 Rs from D 1 Rs. To validate its selectivity, we used HEK293 cells that were stably transfected with either D 1 R or D 5 R cDNA and expressed these receptors at normal physiological concentrations, measured at 3 pmoles/mg membrane protein.…”
Section: Resultsmentioning
confidence: 99%
“…The newly synthesized derivative 3 showed high affinities similar to the lead LE404, displaying nanomolar affinities for all dopamine receptor subtypes. Its dibrominated derivative 4, though exhibiting almost a fivefold decrease in affinities, still displayed nanomolar ones for all dopamine receptors, except for D 4 . In a functional Ca 2 þ assay, both compounds 3 and 4 were found to possess antagonistic properties towards the dopamine receptors.…”
mentioning
confidence: 99%
“…Dibenz [d,g]azecines are a novel class of dopamine receptor antagonists, which are distinguished by their new chemical structure, as well as their high affinities for dopamine receptors, predominantly for the D 1 family [3] [4]. SAR Studies on this new class of compounds revealed that derivatives that encompass a dibenz[d,g]azecine moiety as the backbone structure and bear a OH substituent at C(3) (e.g., compound 1; LE404; Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation